Constitutional Question (Antara Realitas Politik dan Implementasi Hukumnya) - Hamidi, Jazim; Lutfi, Mustafa (Jurnal Konstitusi, 2010)
The emergence of political  and  constitutional  law  discourses,  side by side with the growth of democracy in Indonesia, is developing progressively and dynamically. In reality, this nation  is  under  great tests which determine whether the state is still holding its constitutional commitment on upholding the rule of law.  In the other side, the face of  law enforcement in this state is under an immense storm of urgent issues that need immediate solution which is: can this state provide “justice” unto all of its citizens? This issue is a huge homework for all the nation’s elements in the  future.The establishment of the Constitutional  Court  which  regulated  in the 1945 Constitution surely related to the constitutional reformation which deemed as a necessity and an important agenda that should be applied fundamentally. The existence of the Constitutional Court in the constitutional system of the Republic of Indonesia simultaneously casting new hopes for any justice-seekers. The surfacing question now is will the Constitutional Court capable in faithfully guarding the democracy  and fair constitutionality in the verge of society that has already loose confidence towards justice institution? This simple and short writing attempts to study and discuss on constitutional question, including   on how its political reality and its legal implementation in Indonesia,    and also a slight hope of this writing in enriching the references for any justice-lovers in this  nation.